ANALYSIS OF DETERMINANTS OF WASTING INCIDENCE AMONG CHILDREN AGED 12–59 MONTHS IN THE WORKING AREA OF KAYU GADANG PUBLIC HEALTH CENTER IN 2025 : WASTING INCIDENCE AMONG CHILDREN - Ofalitna, Yozha; Purnakarya, Idral; Azrimaidaliza, Azrimaidaliza (STIKes Mandala Waluya Kendari, 2025)
Background: Wasting is a condition of acute undernutrition where a toddler's weight is not appropriate for their height, or the z-score is below -2SD. This study aims to analyze the determinants of wasting among children aged 12–59 months in the working area of Kayu Gadang Public Health Center in 2025. Methods: This research uses a mixed methods approach, which is a combination of quantitative and qualitative methods. The quantitative method applies a cross-sectional approach, while the qualitative method uses a case study approach. The strategy used is the Convergent Parallel Design, in which both quantitative and qualitative data are collected and analyzed simultaneously (in parallel). The sampling technique applied is proportional random sampling, with a total of 104 samples. Data analysis in this study includes multivariate analysis using the Backward LR test. Results: The results show that energy intake (p-value 0.001), protein intake (p-value 0.001), carbohydrate intake (p-value 0.003), fat intake (p-value 0.005), infectious disease (p-value 0.647), mother's knowledge (p-value 0.001), completeness of immunization (p-value 0.004), and environmental sanitation (p-value 0.001) are statistically significantly associated with wasting among children aged 12–59 months. Family income (p-value 0.647), mother's education (p-value 0.070), and exclusive breastfeeding history (p-value 0.211) are not statistically significantly associated with wasting in this age group. Multivariate analysis showed that the most dominant factor associated with wasting was protein intake. Conclusion: There is a significant relationship between macronutrient intake (energy, protein, carbohydrates, fat), infectious diseases, maternal knowledge, completeness of immunization, and environmental sanitation with the incidence of wasting. The most dominant factor is protein intake.